Methodology for analyzing episodic events - Eisen, Ellen A. (Scandinavian Journal of Work, Environment & Health, 1999)
Many health outcomes of interest to occupational epidemiologists are common recurrent health events. Epidemiologic approaches to the study of such health events are reviewed. Episodic events are considered to be events that occur at a distinct point in time - either with sudden onset or the sudden crossing of a threshold of detection - and they must be reversible events that can recur in the same person in response to a proximate trigger. Studying such health events poses 4 challenges to existing methods: (i) key epidemiologic concepts, such as incidence, do not naturally accommodate recurrent events, (ii) study designs must capture time-varying exposures, (iii) statistical models must be able to handle correlated outcomes, and (iv) feedback bias must be addressed. In response, methods such as longitudinal studies, case-crossover designs and generalized estimating equations are identified as appropriate tools.
Keywords: case-crossover study; correlated outcomes; epidemiology; exposure-response models; longitudinal study; occupational health; repeated measure